2018
DOI: 10.1177/1479972318775422
|View full text |Cite
|
Sign up to set email alerts
|

Depression is a major determinant of both disease-specific and generic health-related quality of life in people with severe COPD

Abstract: The quality of life of patients with chronic obstructive pulmonary disease (COPD) decreases significantly as the disease progresses; those with severe COPD are affected most. This article investigates predictors of the disease-specific and generic health-related quality of life (HRQL) in patients with severe COPD. This multicentre prospective cross-sectional study enrolled 80 patients with severe COPD. At enrolment, all patients completed a disease-specific instrument, the St George's Respiratory Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Chronic kidney disease patients suffer from both physical and psychological symptoms which may emerge at different stages during the course of the disease [26]. Jang et al (2019) assessed the HRQOL of patients with severe chronic obstructive pulmonary disease (COPD) using SF 36 study instrument and the PCS and MCS were 56.7 and 69.5 indicating that the HRQOL of CKD patients is much worse compared to COPD [27]. Similarly two international studies done to assess the HRQOL of stroke [28] and chronic heart failure [29] revealed that the stroke patients had relatively low HRQOL and chronic heart failure patients had a similar HRQOL when compared to the results of our study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease patients suffer from both physical and psychological symptoms which may emerge at different stages during the course of the disease [26]. Jang et al (2019) assessed the HRQOL of patients with severe chronic obstructive pulmonary disease (COPD) using SF 36 study instrument and the PCS and MCS were 56.7 and 69.5 indicating that the HRQOL of CKD patients is much worse compared to COPD [27]. Similarly two international studies done to assess the HRQOL of stroke [28] and chronic heart failure [29] revealed that the stroke patients had relatively low HRQOL and chronic heart failure patients had a similar HRQOL when compared to the results of our study participants.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is the fourth most common cause of death in the United States 1 . Anxiety, depression, and loneliness are commonly recognized psychologic comorbidities of COPD 2, 3, 4. Quality of life in patients with COPD is affected by these factors and comorbidities leading to an inability to engage in activities, decreased exercise capacity, and anxiety/depression 4, 5…”
mentioning
confidence: 99%
“…26 However, in addition to the clinical aspects, it is also useful to underpin that emotional and social wellbeing are involved in COPD management. As the disease progresses, it becomes more difficult to carry out even the simplest daily activities, so much so that only 30.6% of COPD patients say they are satisfied with their life [27]. According to this view, our data demonstrated that three-month, twice-weekly of CRT, as compared to baseline condition was effective in reducing perception of anxiety, depression and stress levels and increasing well-being and vitality in COPD patients.…”
Section: Discussionmentioning
confidence: 57%